Financial Management Practices and Small-Scale Businesses' Profitability, from the Viewpoint of Kabale Municipality, Uganda - Marus Eton; Fabian Mwosi; Eliab Byamukama Mpora (goodwood publishing, 2022)
Purpose: The study's goal was to investigate how financial management practices impact small businesses' profitability. Research methodology: Descriptive and correlational research designs were used in the study. The study used a multi-regression analysis to estimate how financial management practices impact profitability. Results: The research showed that financial management strategies had a big effect on profitability. Management of working capital and cash has a substantial correlation with profitability, according to the evidence. The study suggests that in order to see improvements in their profitability levels, small businesses should establish strong financial management methods. Owners of small businesses must pay close attention to the dynamics of their working capital and cash management because these factors have a significant impact on their profitability levels. To balance operating costs and profitability, small firms should think about cost-cutting measures. Limitations: This study was only conducted within Kabale Municipality and future studies should be conducted in the entire region. Contribution: The study identified a trio of factors – operational expenses, microeconomic factors, and individual characteristics that constrain profitability.